2008
DOI: 10.1111/j.1440-1797.2008.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Shorter break‐in period is a viable option with tighter PD catheter securing during the insertion

Abstract: After a tight catheter securing during the insertions, overall pericatheter leak incidence remained low in the whole study cohort, and it did not worsen despite a shorter break-in period. Future studies with larger patient numbers are needed to validate the role of shorter break-in period in PD practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
0
27
0
2
Order By: Relevance
“…Shame et al [24] reported that after a tight catheter was secured during the insertion, the overall incidence of peri-catheter leakage remained low in the entire study cohort, and the incidence of peri-catheter leakage did not increase despite a shorter break-in period. Povlsen and Ivarsen [5] retrospectively described how acute APD was initiated using a standard prescription for a 12-h overnight APD in the supine position immediately after PD catheter placement and compared short-term outcome measures and dialysis-related complications between urgent-start and planned-start patients.…”
Section: Discussionmentioning
confidence: 99%
“…Shame et al [24] reported that after a tight catheter was secured during the insertion, the overall incidence of peri-catheter leakage remained low in the entire study cohort, and the incidence of peri-catheter leakage did not increase despite a shorter break-in period. Povlsen and Ivarsen [5] retrospectively described how acute APD was initiated using a standard prescription for a 12-h overnight APD in the supine position immediately after PD catheter placement and compared short-term outcome measures and dialysis-related complications between urgent-start and planned-start patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lobbedez et al (14) reported that only 2 of 34 unplanned PD patients (median break-in period: 4 days) experienced a peritoneal leak. Sharma et al (15) showed that, after using a technique to more tightly secure the PD catheter during insertion (n = 48), the overall incidence of pericatheter leak remained low despite a shorter break-in period (<7 days). Similarly, a recent study from Taiwan suggested that early PD initiation (<14 days) in patients undergoing surgical implantation of a Tenckhoff catheter was not associated with an increased number of complications (16).…”
Section: Discussionmentioning
confidence: 99%
“…The early start of peritoneal dialysis, with break-in periods of shorter than 2 weeks, increasingly has been accepted as an option for patients in need of urgent dialysis. Based on recent studies with a very low incidence of leakage, an early start is acceptable for catheters inserted with technique modifications to ensure a water tight seal around the catheter [9,19].…”
Section: Discussionmentioning
confidence: 99%